2013
DOI: 10.1024/0300-9831/a000176
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Some Micronutrients and Congenital Malformations: A Prospective Cohort Study in Healthy Saudi-Arabian First-Trimester Pregnant Women

Abstract: This study highlights the association of CM with the deficiency of certain vitamins and minerals among pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
0
25
1
Order By: Relevance
“…An explanation for the observed iodine deficiency in our study could be related to inappropriate nutrition during prengancy as many studies have indicated that most of Saudi pregnant women were malnourished, and their consumption of essential nutrients were below the recommended daily requirements [35][36][37][38]. Saudi women from the Western region also had significantly low micronutrients intake, thus their offspring had a higher risk of developing birth defects [39][40][41]. Our findings agree with the earlier studies since the use of iodine supplements was only confirmed by a minority (27.6%) of the enrolled pregnant population.…”
Section: Discussionmentioning
confidence: 78%
“…An explanation for the observed iodine deficiency in our study could be related to inappropriate nutrition during prengancy as many studies have indicated that most of Saudi pregnant women were malnourished, and their consumption of essential nutrients were below the recommended daily requirements [35][36][37][38]. Saudi women from the Western region also had significantly low micronutrients intake, thus their offspring had a higher risk of developing birth defects [39][40][41]. Our findings agree with the earlier studies since the use of iodine supplements was only confirmed by a minority (27.6%) of the enrolled pregnant population.…”
Section: Discussionmentioning
confidence: 78%
“…Hence, iodine deficiency in our pregnant population could be related to inappropriate nutrition since many studies have indicated malnourishment in Saudi pregnant women, and they consumed essential nutrients below the recommended requirements [34][35][36][37]. Saudi women from the Western region also had significantly low micronutrients intake, thus their offspring had a higher risk of developing birth defects [38][39][40]. In agreement, the use of iodine supplements was only confirmed by a minority (27.6%) of our pregnant population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted among the Saudi population have also indicated that most of pregnant women were malnourished and their consumption of essential nutrients were below the recommended daily requirements [41][42][43][44]. Saudi women from the Western region had also significantly lower intake of micronutrients during the first trimester, thus their offspring had an increased risk of developing birth defects [45][46][47]. Our findings agree with the earlier observations since they showed that only 27.6% of the enrolled pregnant population were using iodine supplements, which was associated with significantly lower risk of developing iodine deficiency during pregnancy.…”
Section: Discussionmentioning
confidence: 99%